Design of three-component one-dimensional photonic crystals for alteration of optical contrast and omni-directional reflection - PEROVA, TANIA (My University, 2010)
In this study, three-component One-Dimensional (1D) Photonic Crystal (PC) structures were investigated by modeling them as two-component PCs with an additional regular layer. The Gap Map approach and the Transfer Matrix Method were used in order to mathematically describe these structures. The introduction of a third component to a 1D PC allows manipulation of the optical contrast to a high degree of precision by varying the thickness and refractive index of the additional layer. It also partially reduces the area of the photonic band gaps (PBGs) on the gap map, leaving the remainder of the PBG area unchanged from that of the gap map for the original, two-component, PC. Using this approach to decrease the optical contrast in photonic crystals allows omni-directional bands to be obtained in highcontrast periodic structures constructed from, for example, an array of silicon and air.
PUBLISHED
Keywords: Optics; 1D Photonic Crystal; Tunable Photonic Crystal; Multi-component Photonic Crystal; Photonic Band Gap; Photonic Gap Map; Nanoscience & Materials